1988
DOI: 10.1007/bf00265372
|View full text |Cite
|
Sign up to set email alerts
|

Blood glucose may condition factor VII levels in diabetic and normal subjects

Abstract: Summary. Increased factor VII levels have been reported in Type 1 (insulin-dependent) diabetic subjects. A direct correlation between fasting plasma glucose and factor VII level was found to exist in both diabetic and normal subjects. Inducedhyperglycaemia was able to increase factor VII levels in both diabetic patients and normal control subjects while, when euglycaemia was achieved in diabetic patients, factor VII values returned to normal range. This study shows that the level of factor VII may be directly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
1
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(54 citation statements)
references
References 12 publications
3
48
1
2
Order By: Relevance
“…In some studies the correlation between plasma triglyceride and VIIc was found to be genotype specific [9, 10, 15±17] suggesting an interaction between genetic and environmental influence. A positive correlation between fasting plasma glucose and factor VII level has also been reported [18], and VIIc levels are increased in patients with Type II diabetes mellitus especially in the presence of microalbuminuria or albuminuria [19]. In a study of 95 Caucasian Type II diabetic patients, the R/Q353 genotype was found to contribute to 12 % of the variance in VIIc levels.…”
mentioning
confidence: 79%
“…In some studies the correlation between plasma triglyceride and VIIc was found to be genotype specific [9, 10, 15±17] suggesting an interaction between genetic and environmental influence. A positive correlation between fasting plasma glucose and factor VII level has also been reported [18], and VIIc levels are increased in patients with Type II diabetes mellitus especially in the presence of microalbuminuria or albuminuria [19]. In a study of 95 Caucasian Type II diabetic patients, the R/Q353 genotype was found to contribute to 12 % of the variance in VIIc levels.…”
mentioning
confidence: 79%
“…35,36 Since diabetic patients have been reported to have an increased thrombotic tendency, 16 we investigated whether one of the two diets could adversely affect the risk for thrombosis while improving the risk for atherosclerosis. We measured thrombotic factors that have been reported to be abnormal in diabetes, like TPA, factor VII, fibrinogen, [37][38][39][40] and PAI, 20 and/or factors that have been reported to be affected by dietary manipulations, like factor VII 41 and PAI. 42 Prothrombin fragment F1.2 was measured as a parameter of the state of thrombotic activation.…”
Section: Discussionmentioning
confidence: 99%
“…It emerges that acute glycemic variations are matched with a series of alterations of coagulation that are likely to cause a thrombosis. This tendency is documented by studies demonstrating that when hyperglycemia is induced, a shortening of the fibrinogen half-life (41) and an increase in fibrinopeptide A (42,43), in fragments of prothrombin (44), in factor VII (45), and in platelet aggregation (46) can be found in both normal and diabetic subjects. These data indicate that during experimental hyperglycemia, the coagulation is activated.…”
Section: Postprandial Hyperglycemia and Diabetesmentioning
confidence: 91%